Biomass-Derived Ternary-Doped Porous Carbon Electrodes for Li-Ion Capacitors: Rational Preparation and Energy-Storage Mechanism Study. Issue 4 (12th April 2021) - Jiang, Zepeng; Liu, Mengyue; Zhu, Feng; Song, Weihao; Zhang, Zhengping; Dou, Meiling; Niu, Jin; Wang, Feng
Abstract : Owing to the hybrid energy-storage features, Li-ion capacitors (LICs) inherit appealing properties from secondary batteries and supercapacitors, including high power density, high energy density and good cycling stability. However, incompatible kinetics between anode and cathode limit the performance improvement of the LICs. Moreover, the energy-storage mechanisms of carbon electrodes for LICs need to be further explored. Herein, we have prepared two ginkgo leaf-derived porous carbons (GLPCs) and used them as LIC electrodes. As resourceful biomass materials, ginkgo leaves have numerous O, N, S-enriched organics (e.g., flavonoids, alkaloids and thiophenes). By direct pyrolysis of the ginkgo leaves, ternary doped GLPCs are obtained without using additional dopants. The porosities, heteroatoms and defects for the GLPCs are tailored based on electrode requirements. The GLPCs obtained at 600 and 900 °C are specifically employed as the anode and cathode materials for LICs, respectively. The GLPC electrodes show good performance in half cells and their energy-storage mechanisms are interpreted by detailed ex situ and in situ experiments. DFT calculation results reveal that only specific heteroatom doping can enhance Li + and PF6 − storage. Because of compatible electrode kinetics, the assembled LIC using the GLPC electrodes delivers high energy (118 Wh kg −1 ), high power (31.6 kW kg −1 ) and long lifespan.